TEPUNG TAPIOKA SEBAGAI PEREKAT DALAM PEMBUATAN ARANG BRIKET - Nuwa Nuwa; Prihanika Prihanika (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
The use of wood as a fuel and energy source has been since the time of our ancestors first and until now still widely used mainly by rural communities, as well as people in Bukit Rawi for the middle class down. Bukit Rawi KWP group as a partner located in Bukit Rawi village amounted to 4 (four) people, group members are housewives and as rattan wicker craftsmen. The science and technology applied to KWP (Kelompok Wanita Perajin) Bukit Rawi is introducing tapioca starch as an adhesive material and introducing briquette charcoal making technique as an alternative fuel. The introduction of science and technology to Bukit Rawi KWP provides new knowledge and is an additional business opportunity so they are very interested.